Chiroptical properties of bilirubin-serum albumin binding sites - Goncharova, Iryna; Orlov, Sergey; Urbanová, Marie (Chirality, 2013)
Although the interactions between bilirubin and serum albumin are among the most studied serum albumin-ligand interactions, the binding-site location and the participation of bilirubin-serum albumin complexes in pathological and physiological processes are under debate. In this article, we have benefited from the chiral structure of bilirubin and used CD spectroscopy to characterize the structure of bilirubin bound to human and bovine serum albumins. We determined that in a phosphate buffer at pH 7.8 there are three binding sites in both human and bovine serum albumins. While the primary binding sites in human and bovine serum albumins bind bilirubin with P- and M-helical conformations, respectively, the secondary binding sites in both albumins bind bilirubin in the P-helical conformation. We have shown that the bonding of bilirubin to the serum albumin matrix is a more favorable process than the self-association of bilirubin under the studied conditions, with a maximum of three bound bilirubins per serum albumin molecule. Although bilirubin bound to the primary binding site has attracted the most attention, the presented results have documented the impact of the secondary binding sites which are relevant in the displacement reactions between BR and drugs and in the phenomena where bilirubin plays antioxidant, antimutagenic, and anti-inflammatory roles.